2009
DOI: 10.1124/mol.109.061788
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ligand-Mediated Selective Modulation of Aryl Hydrocarbon Receptor Activity

Abstract: The concept of selective receptor modulators has been established for the nuclear steroid hormone receptors. Such selective modulators have been used therapeutically with great success in the treatment of cancer. However, this concept has not been examined with regard to the aryl hydrocarbon receptor (AHR) because of the latent toxicity commonly associated with AHR activation. AHR-mediated toxicity is primarily derived from AHR binding to its dioxin response element (DRE) and driving expression of CYP1 family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 30 publications
3
66
0
Order By: Relevance
“…The AHR is a ligand-activated receptor that not only plays a role in mediating the toxicity of TCDD and related compounds but is also a potential target for the treatment of several diseases including autoimmune diseases, various inflammatory conditions, and cancer (McDougal et al, 2001;Quintana et al, 2008Quintana et al, , 2010Zhang et al, 2009Zhang et al, , 2012DiNatale et al, 2010bDiNatale et al, , 2011Murray et al, 2010;O'Donnell et al, 2010;Kiss et al, 2011;Li et al, 2011;Opitz et al, 2011;Singh et al, 2011). Depending on the tissue or cell, AHR agonists or antagonists may be required, and there is also evidence that the effects of various AHR-active compounds are structure-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AHR is a ligand-activated receptor that not only plays a role in mediating the toxicity of TCDD and related compounds but is also a potential target for the treatment of several diseases including autoimmune diseases, various inflammatory conditions, and cancer (McDougal et al, 2001;Quintana et al, 2008Quintana et al, , 2010Zhang et al, 2009Zhang et al, , 2012DiNatale et al, 2010bDiNatale et al, , 2011Murray et al, 2010;O'Donnell et al, 2010;Kiss et al, 2011;Li et al, 2011;Opitz et al, 2011;Singh et al, 2011). Depending on the tissue or cell, AHR agonists or antagonists may be required, and there is also evidence that the effects of various AHR-active compounds are structure-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, MCDF did not inhibit TCDD-induced antiestrogenic effects in the rodent uterus or human breast cancer cells but acted as an AHR agonist (Astroff and Safe, 1991;Zacharewski et al, 1992), and subsequent studies showed that MCDF also inhibited ERpositive and ER-negative breast cancer cell and tumor growth (McDougal et al, 2001;Zhang et al, 2009Zhang et al, , 2012. Thus, MCDF was one of the first compounds characterized as a selective AHR modulator (SAhRM) that exhibits tissue-selective AHR agonist or antagonist activities (Astroff and Safe, 1991;Zacharewski et al, 1992;McDougal et al, 2001;Zhang et al, 2009Zhang et al, , 2012, and several other AHR antagonists and SAhRMs have been identified (Boitano et al, 2010;Murray et al, 2010Murray et al, , 2011Zhao et al, 2010;Smith et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although AhR complexes clearly interact with the canonical AhR binding site , recent data indicate noncanonical recognition sequences as well (Huang and Elferink, 2012), suggesting the likelihood that the AhR controls transcription of significantly more genes than previously appreciated. It is striking that several AhR protein interactions are only triggered by specific AhR ligands (Boronat et al, 2007;Zhang et al, 2008;Murray et al, 2010), suggesting that some transcriptional partners of AhR are recruited in a ligand-specific manner.…”
Section: A Genomic Pathways Of Aryl Hydrocarbon Receptor Signalingmentioning
confidence: 99%
“…The recent characterization of an anti-inflammatory SAhRM, which represents a novel subset of AHR ligands with the capacity to dissociate non-DRE dependent antiinflammatory action of AHR from potentially undesirable DRE-mediated transactivation points to the amelioration of inflammatory conditions through pharmacological modulation of AHR (Murray et al, 2010c). The modulation of AHR and resultant beneficial effects has also been demonstrated with AHR agonists such as TCDD in diminishing inflammatory parameters associated with a genetic model of diabetes ).…”
mentioning
confidence: 99%